Mammalian Sirtuins and Their Relevance in Vascular Calcification - Pan, Xinyue; Pi, Caixia; Ruan, Xianchun; Zheng, Hanhua; Zhang, Demao; Liu, Xiaoheng (Frontiers in Pharmacology, 2022)
Cardiovascular diseases are a group of diseases with high morbidity and mortality that affect millions of people each year. Vascular calcification (VC) is an active process that involves the mineral deposition of calcium-phosphate complexes. VC is closely related to cardiovascular diseases, such as hypertension, heart failure, and calcific aortic stenosis, and is a type of ectopic calcification that occurs in the vessel walls. The sirtuins (silent mating-type information regulation 2; SIRTs), are a family of histone deacetylases whose function relies on nicotinamide adenine dinucleotide (NAD+). They have non-negligible functions in the regulation of energy metabolism, senescence, apoptosis, and other biological processes. Sirtuins have important effects on bone homeostasis and VC processes that share many similarities with bone formation. Sirtuins have been confirmed to deacetylate a variety of target proteins related to the occurrence and development of VC, thereby affecting the process of VC and providing new possibilities for the prevention and treatment of cardiovascular diseases. To facilitate the understanding of vascular calcification and accelerate the development of cardiovascular drugs, we reviewed and summarized recent research progress on the relationship between different types of sirtuins and VC.